Cell wall-associated ROOT HAIR SPECIFIC 10, a proline-rich receptor-like kinase, is a negative modulator of Arabidopsis root hair growth - Hwang, Youra (J Exp Bot, 2016)
Plant cell growth is restricted by the cell wall, and cell wall dynamics act as signals for the cytoplasmic and nuclear events of cell growth. Among various receptor kinases, ROOT HAIR SPECIFIC 10 (RHS10) belongs to a poorly known receptor kinase subfamily with a proline-rich extracellular domain. Here, we report that RHS10 defines the root hair length of Arabidopsis thaliana by negatively regulating hair growth. RHS10 modulates the duration of root hair growth rather than the growth rate. As poplar and rice RHS10 orthologs also showed a root hair-inhibitory function, this receptor kinase-mediated function appears to be conserved in angiosperms. RHS10 showed a strong association with the cell wall, most probably through its extracellular proline-rich domain (ECD). Deletion analysis of the ECD demonstrated that a minimal extracellular part, which includes a few proline residues, is required for RHS10-mediated root hair inhibition. RHS10 suppressed the accumulation of reactive oxygen species (ROS) in the root, which are necessary for root hair growth. A yeast two-hybrid screening identified an RNase (RNS2) as a putative downstream target of RHS10. Accordingly, RHS10 overexpression decreased and RHS10 loss increased RNA levels in the hair-growing root region. Our results suggest that RHS10 mediates cell wall-associated signals to maintain proper root hair length, at least in part by regulating RNA catabolism and ROS accumulation.